The Critique toward Uṣūl al-Fiqh Literacy of 1890–2023: An Offer for Development - Khoir, Tholkhatul; Munawaroh, Lathifah; bin Hassan, Zainudin (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Critique of uṣūl al-fiqh literacy is very crucial. The scarcity of critique can lead to the risk of intellectual stagnation and an inability to address the legal needs of a constantly changing society, simultaneously causing a lack of resonance with reconstructive ideas. The study aims: 1) to explore evidence of the scarcity of studies criticizing uṣūl al-fiqh from 1890 to 2023; 2) to explain the factors influencing the scarcity of critical works, and 3) to propose steps for the reconstruction of uṣūl al-fiqh. The data sources for this article are works collected from web publishers, digital libraries, and search engines. The data obtained was mapped and analyzed, and its trends were recorded. This study finds that during the period 1890-2023, criticism was the rarest aspect in uṣūl al-fiqh literature. The factors causing the scarcity of critique vary and complement each other, involving scholarly elements, uṣūl al-fiqh factors, and surrounding policies. Although criticism of uṣūl al-fiqh is relatively rare, it does not mean there is no space for reconstruction. Through this study, readers can understand the recent developments in uṣūl al-fiqh and assess the extent to which criticism has been undertaken while reflecting on how reconstruction can be initiated once again.